TINGKAT PENGETAHUAN PERAWAT DENGAN EFEKTIVITAS PENERAPAN MPKP DI RSUD H. A. SULTHAN DAENG RADJA KABUPATEN BULUKUMBA - Muriyati; Safruddin (Jurnal Kesehatan Panrita Husada, 2017)
Knowledge is one of the factors that influence the implementation of the Professional Nursing Practice Model (MPKP). The phenomena and incidents that occurred in the Seruni treatment room showed that the application of MPKP was still not effective. Where there are some nurses who do not know what MPKP is. The purpose of this study was to determine the relationship of the level of knowledge of nurses about MPKP with the effectiveness of implementing MPKP in Seruni Room of H. Andi Sulthan Daeng Radja District Hospital in Bulukumba 2016. This type of research is an Analytical Observational study with a Cross Sectional design. The population in this study were all nurses in the Seruni Room of the H. Andi Sulthan Daeng Radja Hospital in Bulukumba Regency which numbered 30 people. The sampling technique in this study is the Total Sampling method with a sample of 30 respondents. The statistical test used was the Fisher-Extract Test. The results obtained that, in the form of nurses' knowledge level about MPKP with the effectiveness of the application of MPKP with a value of p = 0.045 <p (0.05). The results show that respondents who have a good level of knowledge are 10 respondents (33.3%) and respondents who have a lack of knowledge level are equal to 20 respondents (66.7%). Effective MPKP implementation was 12 respondents (40%) and ineffective MPKP application was 18 respondents (60%). With the conclusion that there is a relationship between the level of nurses' knowledge about MPKP with the effectiveness of implementing MPKP in the Seruni Room of the H. Andi Sulthan Daeng Radja District Hospital in Bulukumba 2016. Suggestions from this research are expected to be an effort to develop a model of professional nursing practice (MPKP) in each hospital, especially to continue to encourage concrete steps by continuing to increase the frequency of MPKP training for nurses so that the application of MPKP will be continuous with the good quality of service obtained by patients in the hospital.